Challenges and Considerations Related to Studying Dementia in Blacks/African Americans. - Ighodaro, Eseosa T; Nelson, Peter T; Kukull, Walter A; Schmitt, Frederick A; Abner, Erin L; Caban-Holt, Allison; Bardach, Shoshana H; Hord, Derrick C; Glover, Crystal M; Jicha, Gregory A; Van Eldik, Linda J; Byrd, Alexander X; et al. (J Alzheimers Dis, 2017)
Blacks/African Americans have been reported to be ∼2-4 times more likely to develop clinical Alzheimer's disease (AD) compared to Whites. Unfortunately, study design challenges (e.g., recruitment bias), racism, mistrust of healthcare providers and biomedical researchers, confounders related to socioeconomic status, and other sources of bias are often ignored when interpreting differences in human subjects categorized by race. Failure to account for these factors can lead to misinterpretation of results, reification of race as biology, discrimination, and missed or delayed diagnoses. Here we provide a selected historical background, discuss challenges, present opportunities, and suggest considerations for studying health outcomes among racial/ethnic groups. We encourage neuroscientists to consider shifting away from using biologic determination to interpret data, and work instead toward a paradigm of incorporating both biological and socio-environmental factors known to affect health outcomes with the goal of understanding and improving dementia treatments for Blacks/African Americans and other underserved populations.